Cybersecurity Issues in ASEAN Country for Society 5.0: Bibliometric Analysis on Scopus Databases - Alfirna Rizqi Lahitani; Adkhan Sholeh; Eriksa Gutama (International Journal of Politic, Public Policy and Environmental Issues, 2023)
Implementation of Society 5.0 was adopted in various countries, including ASEAN. The abbreviation of ASEAN is the Association of Southeast Asian Nations with a total of ten member countries, mainly to promote regional peace and security. The development of decentralized data and communication that has spread across various media and channels has had a positive impact considering ASEAN's role as a link for many investors in various lines such as banking, transportation, e-commerce, telecommunications, and shipping, but it has also raised new concerns about cybercrime. Without supervision, government data including confidential information can be stolen due to cybercrime. It can be a threat to countries that are the target of terrorist attacks or wars through cyberattacks. Cyber security is a concern, without monitoring, the potential for cyberattacks and crimes will become a threat at any time. This study will analyze the development of cybersecurity in ASEAN countries in the Society 5.0 era using a bibliometric approach on several studies in Scopus indexed journals. The research phase begins with data collection using the Publish or Perish (PoP) application, data processing using the Mendeley and Ms. applications. Excel with the aim of selection so that the data is ready to be processed, then analyzed with the VOSviewer application. Based on the results of network visualization analysis, it was found that the keywords that appear the most in each cluster are: ‘ASEAN-civil society', cloud-storage', 'attack-cyberspace-defense', and 'big-data'. This cluster represents the "research stream" of cybersecurity and society. The keywords that appear are based on co-occurrence. The results of the analysis are expected to provide an overview of the latest research themes in the field of cybersecurity and international relations.